The effectiveness of farm programmes on Bangladesh Betar in educating farmers. (2nd September 2017) - Hasan, Md. Mahedi; Mondal, Md. Nazrul Islam; Islam, Md. Nurul; Hoque, Md. Aminul
ABSTRACT: Farm programmes (FPs) of varied categories have been developed and aired over several decades by Bangladesh Betar, the national radio of Bangladesh for the diffusion of farm technologies. The study aimed to produce an in-depth academic evaluation of their effectiveness in educating farmers in Bangladesh. A sample of 465 respondents from the Khulna and Rajshahi divisions in Bangladesh was randomly selected for a questionnaire survey. To analyse the data, relevant documents were collected from the Ministry of Information, the Ministry of Agriculture, and the Ministry of Fisheries and Livestock of Bangladesh. Frequency distribution, z -test, and binary logistic regression analysis were used as statistical tools. The farm knowledge levels of the farmers were considered the predictors for evaluating the effectiveness of FPs. The results revealed that 93.33% of the sample did not listen to the FPs, while only very few of the listeners listened regularly. Despite this, at the 'weak' and 'average' levels of knowledge significant differences were noted between listener and non-listener farmers of FPs. The binary logistic regression analysis (Model 1) identified that the farmers who listened to the FPs were likely to acquire farm knowledge 6.62 times more than the farmers who did not listen to the FPs. The farmers who listened to the FPs were likely to have farm knowledge 2.64 times more than the farmers who did not listen to the FPs but consulted with other sources of farming information (Model 2). Similarly, a listener of FPs with farm training was likely to acquire farm knowledge 5.76 times more than a non-listener with farm training (Model 3). The FPs were found to be very effective and could be used to better complement other mechanisms for educating farmers. Regular access to the FPs ought to be ensured through appropriate stimulants for the diffusion of farm technologies.